2004
DOI: 10.1097/01.inf.0000136871.51792.19
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Frequency and Pathogens Causing Acute Otitis Media in 1995–2003

Abstract: In our experience, persistent AOM and AOMTF has decreased in frequency since the introduction of high dose amoxicillin therapy and pneumococcal conjugate vaccination. It appears that H. influenzae has become the predominant pathogen of persistent AOM and AOMTF since universal immunization with the pneumococcal conjugate vaccine. Fewer S. pneumoniae AOM isolates are penicillin-resistant and more H. influenzae are beta-lactamase-producing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
199
1
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 372 publications
(212 citation statements)
references
References 26 publications
9
199
1
3
Order By: Relevance
“…Others report that middle ear fluid from children with AOM in whom symptoms are persistent is sterile in 42% to 49% of cases. 123,182 A change in antibiotic may not be required in some children with mild persistent symptoms.…”
Section: Initial Antibiotic Treatment Failurementioning
confidence: 99%
See 1 more Smart Citation
“…Others report that middle ear fluid from children with AOM in whom symptoms are persistent is sterile in 42% to 49% of cases. 123,182 A change in antibiotic may not be required in some children with mild persistent symptoms.…”
Section: Initial Antibiotic Treatment Failurementioning
confidence: 99%
“…105 In the first few years after PCV7 introduction, H influenzae became the most frequently isolated middle ear pathogen, replacing S pneumoniae. 122,123 Shortly thereafter, a shift to non-PCV7 serotypes of S pneumoniae was described. 124 Pichichero et al 104 later reported that 44% of 212 AOM cases seen in 2003-2006 were caused by H influenzae, and 28% were caused by S pneumoniae, with a high proportion of highly resistant S pneumoniae.…”
Section: Microbiologymentioning
confidence: 99%
“…At any given time, the majority of healthy adults and children over 5 years of age harbor this microorganism as a commensal in the nasopharynx (17,64). H. influenzae is a frequent cause of noninvasive disease, including respiratory infections (48,64) and otitis media (4,56,64). Infection by H. influenzae also produces invasive disease, including epiglottitis, pneumonia, bacteremia, meningitis (54,64), and occasionally endophthalmitis, leading to blindness (2).…”
mentioning
confidence: 99%
“…Otitis media occurs when bacteria migrate from the nasopharynx to the middle ear by the Eustachian tube; thus, nasopharyngeal colonization is a key element in the pathogenesis of infection. A decrease in colonization by vaccine serotypes of the pneumococcus has occurred, along with an increase in colonization by nonvaccine pneumo coccal serotypes, H. influenzae and M. catarrhalis, resulting in a shift in the pathogens that cause otitis media [14,15]. Revai et al demonstrated an increased prevalence of M. catarrhalis in the nasopharynx during episodes of otitis media in children who had received the vaccine compared with episodes prior to the introduction of the pneumococcal conjugate vaccine [16].…”
Section: Effect Of Pneumococcal Conjugate Vaccinesmentioning
confidence: 99%